PTU-131 Prevalence Of Abnormal Liver Functions Tests (lfts) In Obstructive Sleep Apnea (osa) Patients And Change In Lfts After Continuous Positive Airway Pressure (cpap) Therapy. (9th June 2014) - Haider, R; O'Connor, HJ; Azam, M
Abstract : Introduction: Obstructive Sleep Apnea (OSA) is a recurrent obstruction of the upper airways during sleep leading to intermittent hypoxia (IH). OSA is associated with metabolic syndrome and with non-alcoholic fatty liver disease with abnormal liver function tests (LFTs). Aims: We looked at prevalence of abnormal LFTs in OSA patients and effects of CPAP therapy on LFTs. Methods: In this retrospective study we did chart review of 100 patients of OSA who were commenced on CPAP from 2008 to 2013. We noted their age, body mass index (BMI), alcohol intake status, LFTs 3–18 months before and after CPAP therapy, ultrasound findings and their cholesterol levels. Results: Patient's were in the age group of 38–82 with average (ave) age of 57.5 years. There were 24% Women and 76% were men. Ave BMI was 36.4. Epworth S improved from 12.7 to 5.2 after CPAP therapy. Apnea Hypopnea Index improved from 36.17 to 4.52. A total of 59 of 100 OSA patients had abnormal LFTs at the start of CPAP therapy as compared to 35% patients after therapy which included either abnormal Alanine transaminase (ALT), Gamma-glutamyltransferase (GGT) or Alkaline phosphatase or in combination which suggests significant improvement. There were 10 patients with newly abnormal LFTs after therapy. Prior to CPAP 45 of 100 patients had abnormal ALT with average ALT of 58. 27 of 45 patients had ALT improvement. Ave ALT post therapy was 28.18 of 45 patients had no improvement and there were 4 new patients with abnormal ALT at the end of study. 51 0f 100 patients had abnormal GGT and 33 of 51 had improvement post therapy. 18 patients either had worsening or no improvement and there were 6 new patients with abnormal GGT at the end of study. 10 of 100 patients had abnormal Alk p and only 2 had improvement and 8 had no improvement Bilirubin levels of all patients were normal. 37% had fatty liver reported on abdominal ultrasounds. 15 patients had alcohol intake history including patients with occasional intake, Worsening of LFTs noticed in this group. BMI reduced in 7 patients. 5 of 7 patients had LFTs improvement in this group. Remaining patients BMI fluctuated by 1 kg over study period. 52% had high cholesterol. Of 52 patients, 14 patients had improvement in cholesterol and 7 patients had LFTs improved in this group. 8 Patients did not comply with CPAP. There was no change in LFTS in 6 patients with 1 patient it improved and in 1 they worsened. Conclusion: The study showed that overall prevalence of patients with abnormal LFTs was high in OSA patients (i.e. 59%) and there was significant improvement in ALT and GGT as compared to ALK p after CPAP therapy. Study suggests that optimal assessment and treatment of OSA may lead to LFTs improvement and it demands further prospective studies. Disclosure of Interest: R. Haider Employee of: Trinity College, H. O'Connor Consultant for: Clinical Professor in Gastroenterology, M. Azam Consultant for: Gastroenterology.